Medical Expulsive Therapy (MET) for Ureteral Calculi in Children: Systematic Review and Meta-Analysis - Bacchus, Michael W.; Locke, Rachel A.; Kwenda, Elizabeth P.; DeMarco, Romano T.; Grant, Campbell; Bayne, Christopher E. (Frontiers in Urology, 2022)
Background Medical expulsive therapy (MET) is the use of medication to facilitate ureteral stone passage prior to surgical intervention. Practice guidelines for the use of MET in the pediatric population remain limited, primarily due to a scarcity of randomized controlled trials and concerns regarding dosing and side effects. To address this, we conducted a systematic review and meta-analysis to clarify the impact of MET on the spontaneous passage of pediatric stones located within the distal ureter. Methods A narrow scope search using PubMed and Embase with a predefined search strategy was performed in September 2021 to identify all randomized controlled trials involving the use of pediatric MET for stones located in the distal ureter. Raw data from 6 eligible articles were extracted for pooled analysis. Our primary outcome was the overall effect of MET on ureteral calculi passage within 28 days compared to controls. Results The mean age of patients in included studies was 7.6 years-old, with a range of ages 2–18 years old. In the pooled analysis of eligible studies, 235 patients received MET and 176 received placebo. The mean stone size was 6.40 mm in the treatment arm and 6.42 mm in the control arm. Children receiving MET were more likely than controls to experience spontaneous stone passage (Relative risk 1.39 [CI 95% 1.21–1.60]). Considering all included studies, only one child treated with MET withdrew due to medication side effects. Conclusion Our systematic review and meta-analysis of the use of pediatric MET on spontaneous distal ureteral stone passage demonstrates a statistically significant benefit. The benefits of MET are diverse and include, possibly, minimizing exposure to anesthesia and radiation alongside improving surgical outcomes if ureteroscopy must be performed. Given the increasing incidence of ureteral stones in children and the nuances inherent to pediatric surgery due to smaller anatomy, MET represents an opportunity for safer and more effective pediatric stone management.